Power and The Politics of Infrastructure Planning: A Case Study of The Proposed Construction of A High-Speed Rail System in Texas - Baseham, Abdullah Saeed Ali (PT Penjaminan Infrastruktur Indonesia (Persero), 2023)
This paper explores challenges faced by the Texas high-speed rail project on social fronts, focusing on power dynamics and political consequences in infrastructure planning. The research aims to illuminate decision-making processes, stakeholder roles, and the impact of political and economic factors on infrastructure planning. Employing a research approach, data from news, media, and academic sources are analysed to investigate power dynamics and the political landscape surrounding Texas’s high-speed rail system. The study’s findings emphasize the significant power and influence held by private entities such as Texas Central Partners, driving the ambitious rail venture. Additionally, the research underscores the intricate relationships and power struggles among stakeholders—private companies, state governments, interest groups, and local communities—throughout the infrastructure planning journey. The study proposes actionable recommendations derived from research outcomes, intended to guide improved practices in infrastructure planning. Ultimately, this investigation enhances comprehension of power dynamics and political aspects in infrastructure planning, particularly concerning Texas’s proposed high-speed rail system. The insights presented carry implications for policymakers, practitioners, and researchers engaged in infrastructure planning and development. With a focus on fostering fairness and environmental responsibility, this study aspires to provide valuable insights into the nature of power dynamics, facilitating sound infrastructure planning practices.